Indigenous Education Policy, Equity, and Intercultural Understanding in Latin America - Cortina, Regina (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This book is a comparative study of educational policies over the past two decades in Latin America. These policies, enacted through constitutional reforms, sought to protect the right of Indigenous peoples to a culturally inclusive education. The book assesses the impact of these policies on educational practice and the on-going challenges that countries still face in delivering an equitable and culturally responsive education to Indigenous children and youth. The chapters, each written by an expert in the field, demonstrate how policy changes are transforming education systems in Bolivia, Ecuador, Mexico, and Peru. Going beyond the classroom, they highlight the significance of these reforms in promoting intercultural dialogue in Latin American societies. .